Contract farming in Swaziland: peasant differentiation and constraints of land tenure - Levin, Richard (My University, 1987)
Swaziland's Fourth National Development Plan advocates the development of outgrower schemes based on the example of Vuvulane Irrigated Farms as an alternative strategy for rural development (Swaziland government 1985:309). If this recommendation were to be adopted as agricultural policy, it would necessitate land reform in the areas where these schemes are to be established. This is because of the existing division in land ownership between Swazi Nation Land and freehold Title Deed Land. Swazi Nation Land is held by the King "in trust" for "the nation" and allocated through chiefs to Swazi subjects. Private property in land in Swaziland dates to the concessionary era when large scale concessions were made to European land speculators and prospective farmers in the late nineteenth century by King Mbandzeni. Contrary to what has been argued in much of the literature on Swaziland, this land division has not entailed the development of dualism in agriculture, with the "modern" agricultural sector based on freehold title deed land and the "traditional" sector on Swazi Nation Land (SNL). Rather, both the land division and dualism are products of the development of capitalist relations which have generated an uneven and differential development characterised by the evolution of large-scale multinational and South African dominated enterprises on freehold land, and the development of petty commodity production on SNL. One question arising out of the advocation of the development of outgrower schemes and various forms of contract farming in Swaziland relating to land tenure, is whether or not such schemes can be established on SNL. To put it more specifically: is private ownership in land a pre-requisite for the establishment of viable contract farming schemes? This study will show that while freehold land leased out to petty commodity producers is undoubtedly advantageous for the owners of capital, in terms of the extra control which can be exerted over petty commodity producers, this is by no means a pre-requisite for the development of outgrower schemes. While it will be demonstrated that land tenure is not indicative of the form of production which takes place in agriculture, the chief concern of this paper is to examine the extent to which outgrower schemes in Swaziland have succeeded in their stated objectives of bringing "commercial farming" to the peasantry. The key question which emerges is whether or not outgrower schemes facilitate peasant accumulation and create the conditions for the reproduction of a rich and/or middle peasantry. Answers to these questions will be sought through an examination of three outgrower schemes. Two of these, (Vuvulane Irrigated Farms and Mpetsheni Pineapple Settlement Scheme) are on freehold Title Deed Land, while one (Casalee Tobacco Project) is on both freehold and SNL where petty commodity producing participants are based. The paper argues that contract farming and outgrower schemes are best understood in the context of the social relations to which this form of capitalist development in agriculture gives rise. Such schemes have differentiating effects and create the conditions for the reproduction of a middle peasantry, as well as the potential for more systematic accumulation by peasant producers. In Swaziland land tenure both on SNL and freehold title deed land, through restricting the size of land holdings of scheme participants, may have constraining effects on the extent to which accumulation becomes possible for petty commodity producers on such schemes.
African Studies Seminar series. Paper presented August 1987
Keywords: Land titles. Swaziland